Covid-19 in Indonesia: socio-economic impact and policy response - et. al., Farida Nursjanti, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The 2019 Covid-19 Corona virus has had an extremely strong impact in 2020, including Indonesia, on the dynamics of the global economy. In this study the focus is on examining the impact of Covid-19 in Indonesia on GDP growth, Micro Small Medium Entrepreneurs (MSMEs), the tourism sector, employment, and the poverty rate. With the limitation of international and national mobility, it will have a major impact on the level of GDP growth, and the tourism sector which has a large enough contribution and is linked to unemployment and poverty. Economic growth slowed to 2.97% in the first quarter of 2020 and contracted by 5.32% in the second quarter of 2020 (Bank Indonesia, 2020). The Indonesian economy in the fourth quarter of 2020 against the previous quarter experienced a growth contraction of 0.42 percent. Based on a survey conducted by Statistics Indonesia (BPS) of MSMEs in various regions in Indonesia, there were as many as 84 percent of micro and small businesses and 82 percent of medium and large businesses experiencing a decline in income since the Covid-19 pandemic occurred. During 2020, the number of foreign tourist visits to Indonesia reached 4.02 million visits or decreased by 75.03 percent when compared to the number of foreign tourists visiting in the same period in 2019 which totaled 16.11 million visits. The Covid-19 pandemic caused the open unemployment rate which was suppressed at 5.23 percent to increase by 7.07 percent. The percentage of poor people in September 2020 was 10.19 percent, an increase of 0.41 percentage points against March 2020 and an increase of 0.97 percentage points compared to September 2019. The Indonesian government issued various policies in response to Covid-19, including policies for the business world, policies for MSMEs, and policies for the poor in addition to several other policies.